The Application of Islamic Critical Thinking in Inquiry-Based Learning in Traditional Islamic Educational Institutions - Syafruddin, Syafruddin; Muhyiddin, Muhyiddin; Mahmudin Nst, Anjar; Wingkolatin, Wingkolatin; Rintaningrum, Ratna; Aji, Yunita Abdullah (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to examine the application of Islamic Critical Thinking as an approach in the inquiry-based learning model within the traditional Islamic educational environment (dayah), with a case study at Dayah Jamiah Al-Aziziyah Bireuen, Aceh. In the context of the modernization of Islamic education, the reinforcement of critical thinking rooted in Islamic values has become an urgent necessity to shape a generation of santri who are intellectual, reflective, and reasoned. This research employs a qualitative method with a field study approach. Primary data were collected through participatory observation, in-depth interviews with teachers and dayah leaders, and documentation of learning activities. Data sources consisted of key informants (teachers and dayah leaders) and supporting informants (santri). The data analysis technique was conducted inductively through stages of data reduction, data display, and conclusion drawing. The results indicate that the integration of Islamic Critical Thinking values—such as open-mindedness, truth-seeking, and ethics of dialogue—into the inquiry-based learning model significantly enhances active participation, intellectual sensitivity, and the depth of students' understanding of Islamic materials. Moreover, the dayah caretakers and teachers play a central role in guiding the process of critical thinking based on revelation and the Islamic scientific tradition. These findings make a significant contribution to the development of an Islamic education model that is responsive to contemporary challenges while remaining firmly rooted in Islamic values.